KONSEP KELUARGA HARMONIS DALAM BINGKAI SAKINAH, MAWADDAH, WARAHMAH - Masri, Masri (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2024)
This research aims to identify the concept and form of a harmonious family in Islam in terms of sakinah, mawaddah, warahmah. This research is normative research with a qualitative type of research using descriptive analysis methods. The research results show that a harmonious family can be identified from the criteria of mutual understanding, fostering a sense of love with family members, deliberation within the family, forgiving each other's mistakes, and accepting each other's shortcomings between husband and wife. The manifestation of this harmonious family concept in Islam is known by the terms sakinah, mawaddah, warahmah